World War II and German Short Story: A Collection of Urdu Translation - Zaheer Abbas (بازیافت, 2021)
The translations made by Muhammad Salim ur Rehman are a selection of German short stories which are written during or after the World War II.The uniquity of these stories is there intricate form which was discovered by those writers during that era.The purpose of this essay is to introduce the readers of Urdu literarure to their usefulness.Until we unreath the new multi layered narratives, the meaningful interpretation of the oppressive atmosphere be impossible.